2016
DOI: 10.5037/jomr.2016.7303
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Peri-Implantitis: Effect of History of Periodontal Disease and Smoking Habits. A Systematic Review and Meta-Analysis

Abstract: ObjectivesThe purpose of this review was to evaluate whether history of periodontitis and smoking habits could represent a risk factor for peri-implantitis and implant loss.Material and MethodsThis systematic review followed PRISMA guidelines and was registered at the PROSPERO database [registration numbers CRD42016034160 (effect of history of periodontitis) and CRD42016033676 (effect of smoking)]. Broad electronic (MEDLINE) and manual searches were conducted among articles published from January 1st 1990 up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 69 publications
3
56
1
9
Order By: Relevance
“…Although, recent evidence has indicated that history of periodontitis is identified as a predisposing factor for implant loss, 42 peri-implantitis 43 and higher PD and BL around the implants, 44 scarce information is available about its effect on the outcome of RST of peri-implantitis in literature. Although, recent evidence has indicated that history of periodontitis is identified as a predisposing factor for implant loss, 42 peri-implantitis 43 and higher PD and BL around the implants, 44 scarce information is available about its effect on the outcome of RST of peri-implantitis in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although, recent evidence has indicated that history of periodontitis is identified as a predisposing factor for implant loss, 42 peri-implantitis 43 and higher PD and BL around the implants, 44 scarce information is available about its effect on the outcome of RST of peri-implantitis in literature. Although, recent evidence has indicated that history of periodontitis is identified as a predisposing factor for implant loss, 42 peri-implantitis 43 and higher PD and BL around the implants, 44 scarce information is available about its effect on the outcome of RST of peri-implantitis in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is tooth loss caused by an inflammation driven periodontitis that is rarely observed before patient age of 35 to 40 years. 92 Antoun et al 93 showed that the prevalence of early inflammation after implant surgery increased from low levels at the age of the patients below 20 years to higher levels in patients in their 50s, where after the risk of inflammation decreased with further increasing age. Implant treatment to replace missing teeth involves placement of a foreign body into the host tissue that induces a foreign body immune response that contributes to bone encapsulation of the implants, which become osseointegrated.…”
Section: On Factors With Particular Relevance For Oral and Orthopedmentioning
confidence: 99%
“…Implant treatment to replace missing teeth involves placement of a foreign body into the host tissue that induces a foreign body immune response that contributes to bone encapsulation of the implants, which become osseointegrated. [92][93][94][95][96] Thus, patients that lose all teeth early due to severe and treatment resistant periodontitis may in some but not all patients risk greater problems with inflammation and implant failures than others. 92 Antoun et al 93 showed that the prevalence of early inflammation after implant surgery increased from low levels at the age of the patients below 20 years to higher levels in patients in their 50s, where after the risk of inflammation decreased with further increasing age.…”
Section: On Factors With Particular Relevance For Oral and Orthopedmentioning
confidence: 99%
“…Risk Factors for Peri-Implantitis: Effect of History of Periodontal Disease and Smoking Habits. A Systematic Review and Meta-Analysis (Stacchi et al [2]) …”
Section: Resultsmentioning
confidence: 99%